The status of Semeiocardium Zoll. (Balsaminaceae) - Nanda Utami (BRIN Publishing (Penerbit BRIN), 2009)
On the basis of comparison with other characters of two subgenera of the genus Impatiens, Semeiocardium Zoll. is proposed to be best treated as a subgenus of Impatiens (Balsaminaceae). Subgenus Semeiocardium (Zoll.) N. Utami is distinguished from the other two subgenera in the number of locular ovary and its connate wing petals. Subgenus Semeiocardium has 20 species in four sections of Impatiens in the sense of Warburg & Reiche (1896). There are 14 species of Impatiens in section Microcentron Warb., 3 species of section Macrocentron Warb, 2 species of section Brachycentron Warb., and 1 species of section Brevicalcaratae Warb.